Spectrophotometric Estimation of Ceftazidime in Pure and Pharmaceutical Forms - MRUTHYUNJAYASWAMY, B.H.M.; HIREMATH, BASAVARAJ; MALIPATAIL, S.M.; APPALA RAJU, S. (Asian Journal of Chemistry, 2010)
Three new, simple, sensitive and economical methods (I, II and III) have been developed for the quantitative estimation of ceftazidime in bulk and its pharmaceutical formulations. Method I is based on the oxidation followed by complexation between ceftazidime and 2,2' -bipyridine (2,2'-bpd) in presence of ferric chloride to form a blood red coloured chromogen exhibiting λmax at 520 nm. Method II is based on the formation of purple coloured chromogens obtained when drug was diazotised with nitrous acid followed by coupling the resulting diazonium salt with α-naphthol exhibiting λmax 562 nm. Method III is based on the formation of coloured Schiff's base obtained when drug reacted with p-dimethylaminobezaldehyde to form yellow coloured chromogen exhibiting λmax at 410 nm. These methods obeyed Beer's law in the concentration range at 2-10, 10-50 and 10-50 μg/mL, respectively. The results of analysis for the three methods have been validated statistically and by recovery studies. The results are comparable with those obtained with UV spectorphotometeric method is double distilled water and λmax 239 nm.